2018
DOI: 10.1063/1.5012097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of superhydrophobicity on flashover characteristics of silicone rubber under wet conditions

Abstract: Superhydrophobic surface has aroused much interest among researchers due to the low adhesion between water and a substrate surface. This study focuses on the influence of the low adhesion of superhydrophobic surface on flashover characteristics under wet conditions. The flashover experiments were conducted under two different wet conditions. One was placing a constant volume droplet on the silicone rubber. The other one was that silicone rubber was wetted by salt fog. It was found that the adhesion between wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Moreover, due to the low hysteresis of the coating contact angle, water droplets are easy to roll on the superhydrophobic surface. By reducing the surface energy or controlling the micro nano roughness of the solid surface, the fouling problem of the solid surface can be solved, which reflects the low adhesion and is also conducive to the sliding of the liquid on the superhydrophobic surface [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, due to the low hysteresis of the coating contact angle, water droplets are easy to roll on the superhydrophobic surface. By reducing the surface energy or controlling the micro nano roughness of the solid surface, the fouling problem of the solid surface can be solved, which reflects the low adhesion and is also conducive to the sliding of the liquid on the superhydrophobic surface [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Cao et al proposed critical water proportion to determine whether the partial arc will lead to insulation failure [19]. Through theoretical calculation and experimental observation, it was found that the water drops on the hydrophobic surface were elongated by the function of electric field force [20][21][22]. When placed in an AC electric field, the vibration frequency of water drop is faster than that of the applied electric field [22].…”
Section: Introductionmentioning
confidence: 99%
“…Through theoretical calculation and experimental observation, it was found that the water drops on the hydrophobic surface were elongated by the function of electric field force [20][21][22]. When placed in an AC electric field, the vibration frequency of water drop is faster than that of the applied electric field [22]. Compared with water drops on the upper surface of composite material, the force exerted on sheds edge water drops is more complicated, such as gravity, surface tension, and electric field force [23].…”
Section: Introductionmentioning
confidence: 99%
“…The flashover voltage of an insulator is related to its geometrical parameters (length, profile, position, number of insulators and their connection, location, and type of insulator) and electrical parameters (longitudinal dielectric strength and surface electrical resistance). The degree of their individual or simultaneous effect on their electrical performance has been the subject of several research studies in order to end up in an insulator profile with the best electrical performance [3][4][5][6][7][8][9][10][11]. Figure 1c shows the support on which the 10 samples distributed in two rows are suspended vertically.…”
Section: Introductionmentioning
confidence: 99%